Clinical effect of non-convulsive electroconvulsive therapy combined with olanzapine in patients with schizophrenia - Tao, Kecai; Xiong, Qian; Wu, Jinghua (Frontiers in Neurology, 2025)
ObjectiveTo explore the clinical effect of non-convulsive electroconvulsive therapy combined with olanzapine in schizophrenia patients.MethodsFrom September 2021 to August 2023, a total of 112 patients with schizophrenia treated in our hospital were selected as the study participants. These patients were randomly divided into a control group and a research group, with 56 cases in each group. Patients in the control group were administered olanzapine tablets. Based on olanzapine tablets, patients in the research group received non-convulsive electroconvulsive therapy. The psychotic symptoms, severity of schizophrenia symptoms, memory ability, cognitive function, serum BDNF, S100B, and GFAP levels, and incidence of adverse reactions between the two groups were compared.ResultsCompared to the control group, the research group had lower BPRS score, lower PANSS score, higher WMS-IV score, higher BACS score, higher serum BDNF level, lower serum S100B and GFAP levels (p < 0.05). However, there was no significant difference in the incidence of adverse reactions between the two groups (p > 0.05).ConclusionNon-convulsive electroconvulsive therapy combined with olanzapine has a significant effect in the treatment of schizophrenia. It can effectively improve mental symptoms and cognitive function of patients, regulate the levels of serum BDNF and S100B, and has high safety.